ANALISIS MEKANISME PEMUNGUTAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 UNTUK KARYAWAN DI PT. MARABUNTA ADI PERKASA MANADO - Lumanto, Edgar Gilbert; Sabijono, Harijanto; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2018)
Income Tax Article 21 is a tax that is deducted by another party for income in the form of salary, wages, honorarium, allowances, and other payments by name and in any form in connection with work, services, or activities carried out by domestic private taxpayers. On this basis Government Agencies and Companies that pay employees or employees are obliged to apply Article 21 Income Tax calculations to the income received by their employees every month. This research was carried out at PT Marabunta Adi Perkasa Manado. The purpose of the study is to analyze the collection mechanism and Article 21 PPh reporting of PT Marabunta Adi Perkasa Manado whether it is in accordance with the Taxation Law No. 36 of 2008 concerning Income Tax. The research method used in this thesis research is descriptive method whose purpose every data collected is analyzed and then drawn a conclusion and research type used is qualitative descriptive. The research results obtained that the Article 21 PPh collection and reporting mechanism applied by PT Marabunta Adi Perkasa Manado is in accordance with Law No. 36 of 2008 concerning Income Tax.Keywords: Mechanism of Collection, Reporting, Income Tax Article 21.